Lower Extremity Abscess Formation in Premature Infants due to Routine Infant Vaccinations - Yuhang Sun; Surya N. Mundluru; Alice Chu (Case Reports in Pediatrics)
Since the introduction of vaccines, the impact of vaccinations has been immeasurable. Under the current immunization guidelines, infants receive the first of their routine infant vaccinations at 2 months of age. While the benefits of routine infant vaccinations in premature infants have been demonstrated, there is relatively little data on the dosing of these vaccines in premature infants. The medical records of two premature infants who developed intramuscular abscesses after receiving their routine infant vaccinations were reviewed. Both patients developed pain in the area of the injection after receiving their vaccinations. Magnetic resonance imaging findings confirmed the formation of an abscess. No other causes of abscess formation were observed. Both patients required surgical intervention and were treated with a course of antibiotics. To our knowledge, this is the first case report to suggest routine vaccinations as a potential cause of abscess formation in premature infants.